Analisis Pemberdayaan UMKM Melalui Taman Pinka di Desa Susuhbango Kecamatan Ringinrejo Kabupaten Kediri - Endang Siswati; Agus Prastyawan; Weni Rosdiana; Muhammad Khairul Anwar (Policy and Maritime Review, 2025)
This study aims to analyze the empowerment of Micro, Small, and Medium Enterprises (MSMEs) through Taman Pinka in Susuhbango Village and to identify its supporting and inhibiting factors. A descriptive qualitative approach was employed in this research. Data were collected through observation, interviews, and documentation involving the Chairperson of the Village Consultative Body (BPD), the Director of the Village-Owned Enterprise (BUMDes), MSME actors, parking attendants, and visitors. Data were analyzed using the interactive model of Miles and Huberman, focusing on the enabling, empowering, and protecting dimensions proposed by Kartasasmita. The findings indicate that the enabling dimension has been implemented through the provision of business stalls and the creation of economic opportunities, although the distribution of business locations remains uneven. The empowering dimension has been carried out through coaching and training programs; however, these activities have not been evenly distributed and do not fully meet the needs of all MSME actors. The protecting dimension has been implemented through regulations, conflict management, and security measures. Supporting factors include the unique tourism concept and promotional support from the village government, while inhibiting factors include limited funding and supporting facilities. The study concludes that MSME empowerment through Taman Pinka has been implemented relatively well; however, further efforts are needed to strengthen the capacity of MSME actors and improve supporting facilities. Keywords: MSME empowerment, Taman Pinka, enabling, empowering, protecting